Determination of genetic diversity in Acacia modesta germplasm using SDS-PAGE - M. Zahoor; M. Nisar; A. Ur Rahman; W. Ul Bari (Brazilian Journal of Biology, 2022)
Abstract Biochemical markers such as protein are very important to determine genetic diversity among plant species in a given population which in turn is very important for breeders and farmers as they can then easily select the most appropriate variety to grow in a given locality. In this connection, the present study is aimed to evaluate genetic diversity in Acacia modesta germplasm through Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) technique. About 40 genotypes were subjected to SDS-PAGE analysis where a total of 12 polypeptide bands were observed in electrophoretogram. Out of which 16.67% were monomorphic while the remaining 83.33% were polymorphic. Variation found in B-2, 4, 5, 6, 7, 8, 9, 10, 11 and 12, were 20, 22.50, 32.50, 10, 2.50, 22.50, 15, 5, 2.50 and 75% respectively. Locus contribution toward genetic disagreement was 83.33%. Cluster analysis sorted all the genotypes into 9 clusters. The genotypes in one cluster were identical regarding protein profiling and showed less intra-specific genetic variation whereas differences were find from other genotypes.